Effect of Technical Capability on Implementation of Family Planning Projects by Non-Governmental Organizations in Kenya - Sande, Pauline Namukunda; Ogollah, Dr. Kennedy (International Journal of Entrepreneurship and Project Management, 2016)
Purpose: The study sought to establish the effect of technical capability on implementation of family planning projects by Non Governmental Organizations in Kenya. In Kenya, there is a high level of unmet need for family planning and this led to the study hypothesis that technical capabilities may have affected the implementation of family planning projects. Methodology: This study adopted a descriptive survey design. The population of the study was all the 750 registered NGO's in the health sector in Nairobi, Kenya. The study adopted simple random sampling technique to select a sample of 225 NGOs (30% of the population). Primary data was collected using a semi structured questionnaire. Descriptive statistics included the mean and standard deviation while the inferential statistics included a multiple linear regression and bivariate correlation. Results: Technical capabilities and implementation of family planning projects are positively and significant related (r=0.568, p=0.000). The coefficient of determination also known as the R square of 32.2% indicated that the variation in technical capability explains 32.2% of variation in implementation of family planning projects in Kenya. Regression coefficients results show that there is a positive and significant relationship between technical capability and project implementation as supported by beta coefficients of 0.306. Specifically, the results show that increased technical capability by one unit would result to increased implementation of family planning projects by 0.306 units. Unique contribution to theory, practice and policy: From the study findings, it is recommended to NGO managers (practitioners) that technical capability in terms of training should be increased. Policy makers such as NGO Coordination Board should advocate and implement policies geared towards improving technical capabilities of NGOs. The study validates the Lewin change management theory and its applicability in the NGO sector. The revised conceptual framework may offer a fertile ground for developing and improving related studies.